1984
DOI: 10.1001/archotol.1984.00800340058017
|View full text |Cite
|
Sign up to set email alerts
|

Laryngomalacia: A Review and Case Report of Surgical Treatment With Resolution of Pectus Excavatum

Abstract: \s=b\ Laryngomalacia has been described in the medical literature for over 100 years. During this time many different names have been used for the same condition. There have been numerous discussions of symptoms, cause, pathogenesis, relationships to other conditions, hereditary factors, and treatment. The purpose of this study is to historically review the literature, clarify terminology, and describe the clinical aspects of the disease.We also summarize and make conclusions regarding cause, pathogenesis, gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
69
1
9

Year Published

1995
1995
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(79 citation statements)
references
References 26 publications
0
69
1
9
Order By: Relevance
“…In our study, there was no predominance of gender, even though some authors reported predominance of male patients 2,10 . The clinical picture of inspiration stridor found in all our patients with furculum retraction intensified by efforts, is considered the most characteristic by all authors, as well as stridor that may be present since birth or manifest in the first weeks of life.…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, there was no predominance of gender, even though some authors reported predominance of male patients 2,10 . The clinical picture of inspiration stridor found in all our patients with furculum retraction intensified by efforts, is considered the most characteristic by all authors, as well as stridor that may be present since birth or manifest in the first weeks of life.…”
Section: Discussioncontrasting
confidence: 66%
“…Several anatomic changes of the supraglottis are observed in laryngomalacia [2][3][4]. Immaturity of the laryngeal cartilage has been proposed to be a contributing factor [5,6]. Increasing evidence suggests a neurologic etiology: altered sensorimotor integrative function of the larynx leads to neuromuscular hypotonia of the pharyngolaryngeal structures causing supraglottic collapse during inspiration [7].…”
Section: Discussionmentioning
confidence: 99%
“…It is characterized by a dynamic obstruction of the upper airway due to an inward collapse of supraglottic structures during inspiration. Although several theories have been postulated [2][3][4][5][6][7], the exact etiology of laryngomalacia is not fully understood and different factors may contribute to the disease [6,8], notably gastroesophageal reflux [9][10]. Laryngomalacia typically presents with a moderate to high-pitched fluttering inspiratory stridor being more marked during increased air demands.…”
Section: Introductionmentioning
confidence: 99%
“…Schwartz, em 1944, 10 propôs que a laringomalacia grave poderia ser tratada através da ressecção cirúrgica dos bordos laterais da epiglote. Entretanto, foi somente em 1984 que Lane et al 11 , pela primeira vez, propuseram que a laringomalacia grave deveria ser tratada através da ressecção endoscópica da mucosa redundante de uma ou de ambas as aritenóides, e de ressecção das bordas laterais da epiglote. Desde então, vários trabalhos têm mostrado bons resultados com esta técni-ca [12][13][14][15] .…”
Section: Discussionunclassified